"Model 2"—A personal journey in pursuit of creativity and impact. (February 2015) - Hermanson, Dana R.
Abstract: Many have expressed concerns with the lack of innovation and creativity in accounting research, and one particular type of research has come to dominate many of the "elite" journals. In this essay, I discuss my efforts to follow a different path than the traditional "top-tier" archival financial accounting research model. Specifically, I describe two different research career models that one can pursue, which I refer to as "Model 1" and "Model 2". I describe the research development process under Model 2, which begins with a practice question, and contrast it with a possible approach under Model 1, which begins with the acceptable journal outlets. I then discuss some projects and activities during my career that illustrate the Model 2 approach and its benefits. I close with some overall observations about Model 2 and its challenges, as well as the potential for changing the accounting research culture.